STUDI IKONOLOGI PANOFSKY PADA ARSITEKTUR DAN INTERIOR GEREJA KATOLIK INKULTURATIF PANGURURAN - Sitindjak, Ronald Hasudungan Irianto (Institute of Research and Community Outreach - Petra Christian University, 2011)
The Inkulturasi Pangururan Catholic church (GKIP) is a place of worship for Catholics in Pangururan City, Samosir, North Sumatera. The architectural and interior forms are results of inculturation of Catholic traditions with Batak Toba cultures and hence the meaning behind the building elements becomes a very interesting issue of study. This research uses the iconological study method proposed by Panofsky which aims to uncover the meaning contained in an object through a set of desciptional stages that concists of pre-iconography, analysis of iconography and iconological intepretation, in which all of the three stages are inter-connected. Pre-iconography aims to acquire the prime or natural meaning (factual and expressional meaning), analysis of iconography is to obtain the secondary/conventional meaning while iconology is to uncover the intrinsic meaning (symbolical meaning). The prime meaning that was discovered in the stage of pre-iconography reveals that the architectural and interior form of GKIP has simililarities to tradtional houses of Batak Toba, displaying the vernacular Batak Toba style. Meanwhile, the secondary meaning resulted from the iconography stage shows that the spatial and ornamental arragnement inside has undergone transformations, adaptations and even tiggered new meanings that do not exist in Batak Toba traditional houses. And last but not the least, the intrinsic meaning yielded from the iconology stage shows that the meeting of Catholic culture and Batak Toba tradition produced mutual enrichment through the process of inculturation. On one hand for the preservation of Batak Toba culture, and on the other hand for the expression of faith and trust of Pangururan Catholics in Batak Toba culture. Disclosure of this faith will bring changes to the Catholic church, from the Catholic church in the land of Batak Toba to the process of